A case report of platypnea-orthodeoxia syndrome: A rare condition found during diagnostic workup of a patient with embolic stroke of undetermined sources - Mizuma, Keita; Sugimoto, Azusa; Mochizuki, Yasuhide; Shinke, Toshiro; Ono, Kenjiro (eNeurologicalSci, 2022)
Platypnea-orthodeoxia syndrome (POS) is a rare condition wherein the magnitude of the interatrial shunt changes between the sitting and supine positions. We diagnosed POS in a case initially considered to be of embolic stroke of undetermined source and performed emergency foramen ovale closure as definitive management for the patient. In this case, additional risk factors for POS include spinal deformity, meandering of the aorta, and exclusion of the right atrium due to overextension. Transcranial color flow imaging is recommended for the diagnosis of POS because of its sensitivity, specificity, and non-invasiveness. Although POS is an important barrier to effective rehabilitation, early diagnosis and definitive management lead to dramatic clinical improvement. •In POS, the magnitude of the interatrial shunt changes during repositioning.•TC-CFI is recommended for diagnosing POS due to its sensitivity and specificity.•Early diagnosis and definitive management lead to dramatic clinical improvement.